Efeito da fibra solúvel como estratégia terapêutica na mucosite intestinal experimental em camundongo - Bruno Gallotti Costa (2018)
Mucositis is an inflammation of the gastrointestinal mucosa very frequent in patients under chemo- and radiotherapy. Fiber-enriched diets, especially soluble fibers, have shown very important beneficial and immunomodulatory effects for the individual, mainly by inducing the production of short chain fatty acids contributing to intestinal homeostasis. Thus, the aim of this study is to evaluate the effect of high soluble fiber (HF) diet, as well as the effect of the absence of dietary fiber using a zero fiber (ZF) diet, on chemotherapy-induced murine experimental mucositis irinotecan. C57BL/6 mice were fed with control (AIN93), HF and ZF diets for 14 days. Mucositis was induced on day 10 and the animals were sacrificed 4 days after. Mice fed with HFdiet had decreased intestinal permeability after mucositis induction while the ZF diet increased the permeability in comparison with untreated mucositis group. Mucositis induction was associated with myelosuppression and reduced intestine length and administration of HF diet was able to prevent these parameters. Mucositis induction was also associated with increased expression of pro- inflammatory cytokines such as IL-1β and IL-6, and treatment with fiber decreased the expression of these mediators. The induction of mucositis resulted in dysbiosis associated with an increase Enterococcus sp., and the HF diet was able to reduce this population and increase the population of lactic acid bacteria. Interestingly, the absence of fibers in the diet exacerbated the population Enterobacteriaceae and decreased the bacterial diversity of the gut microbiota of mice treated with ZF diet compared to control and untreated mucositis groups. Fiber intake increased the population of Bacteroides sp. and also increased the concentration of acetate in the feces, which, in turn, may be associated with the beneficial effect of the HF diet, since oral treatment with acetate improved some clinical parameters in animals with induced mucositis, such as decreased MPO and EPO activity. Therefore, our results suggest the importance of fiber intake in the composition of the microbiota and maintenance of homeostasis as an important therapeutic strategy for mucositis, and also for understanding the risks that a fiber-deficient diet can bring during chemotherapy.